(untitled) (La U Investiga, 2022)
Introduction: Type II diabetes mellitus is a chronic non-communicable degenerative disease that in recent years has shown to have a great impact worldwide, becoming a public health problem. Objective: To determine the risk for the development of Type 2 Diabetes Mellitus in operational drivers belonging to the "Union of executive taxis of Imbabura UPOTEI" and its relationship with sleep quality in the period March-June 2022. Methodology: An observational, cross-sectional and relational study was carried out in a population of 360 taxi drivers, where a simple random probabilistic sampling was applied, with a sample of 186 drivers, to whom the Findrisk scale and the Pittsburg questionnaire were applied. The data was collected in Excel 2021 and the analysis was performed using the statistical program SPSS 26, the Fisher statistical test was used to establish the relationship between the risk of diabetes and sleep quality. Results: The drivers presented a slightly elevated risk (36%), most of them correspond to men (96.2%), mestizos (94.1%), married (59.1%) and residents of the Ibarra Canton (79%). ). The population had a higher prevalence within the range of 45 years (44.6%), overweight (52.2%), physical inactivity (61.3%), and consumption of fruits, vegetables and cereals (55.9%) . Sleep quality in drivers was good (77.4%). There was a relationship between low risk (32.3%) and high risk (10.8%) with the Pittsburgh questionnaire that assesses sleep quality. Conclusions: In taxi drivers, the risk for the development of diabetes mellitus was slightly moderate. Low and high risk of diabetes was related to sleep quality